Innovative Teaching in the Digital Age; Applying the TPACK Model to Foster Learning Motivation among Primary School Students - Rosa, Ade Tutty Rokhayati; Purba, Jujur; Napitupulu, Martha; Wiyanti, Dwi (Al-Qalam Institue, 2025)
This study aims to describe and critically analyze the implementation of innovative learning based on the Technological Pedagogical Content Knowledge (TPACK) framework in the digital era and to evaluate its influence on enhancing elementary students’ learning interest. Conducted as a case study, the research focused on sixth-grade students at SDN Pekojan 03 and 05 in Jakarta. A qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings reveal that TPACK-based learning strategies foster a more engaging, interactive, and contextually relevant learning environment. The integration of technology with pedagogical strategies and subject matter content significantly enhanced student participation, enthusiasm, and curiosity in the classroom. Moreover, the application of digital learning tools contributed to increased student motivation and active learning behaviors. These results suggest that the TPACK framework provides a practical and effective pedagogical model to address 21st-century learning challenges in primary education. The study highlights the potential of TPACK in supporting the development of student-centered, technology-integrated learning, and offers insights for educators seeking to optimize digital pedagogies in elementary school settings.